The Adverse Effect of Information on Governance and Leverage - Laux, Christian; Lóránth, Gyöngyi; Morrison, Alan D. (Management Science, 2018)
We study the effect that internal information systems have on a firm’s leverage and corporate governance choices. Information systems lower governance costs by facilitating more targeted interventions. But they also generate asymmetric information between firms and their investors. As a result, firms may attempt to signal their superior quality by assuming more leverage. In some circumstances, this can reduce governance incentives and result in inferior outcomes. Investors anticipate this effect, and it renders information systems inefficient. The online appendix is available at https://doi.org/10.1287/mnsc.2016.2599 . This paper was accepted by Amit Seru, finance.